Factors that influnce job turnover intention within hotel industry in Melaka / Isamuddin Ibrahim Shak - Ibrahim Shak, Isamuddin (Faculty of Business and Management, 2018)
The objective of this research is to investigate the job turnover intention among hotel employees in Malacca. It is important for organization in this industry to understand the factors that affect job turnover intention among employees and ways to retain employees. The reason on why I choose this topic is because job turnover intention study is not popular in Malaysia but it has a big impact to the organization. This study also aims to understand the relationship between organizational commitment, organizational justice, job satisfaction, person-organization fit with job turnover intention. The question that will be answered at the end of this study is what is the most significant factor that influence job turnover intention among the independent variables and how this study can help the hotel industry. This study is a survey based on questionnaires as a main tool of data collection. The data collected then were analyzed using SPSS. Results of the analyzed are illustrated in form of tables, bar chart and pie chart for easier understanding. The study has been done in three hotels namely, Hotel Arissa, City Bayview Hotel and Marvelux Hotel. All of the hotels mentioned are located in Melaka Tengah.